Stage one financial accounting - Harrison, W. (Great Britain : Northwick publishers, 1986)
This book is written for the student who is preparing for "O" and "A" levels, BTEC Diplomas and certificates (National & Higher), first year Business Studies Degrees and the first stages (Part 1/Foundation) of any business professional examination.
Includes bibliographic references and index
hza 27/09/2018, rpm 25/01/2019
Loans
Keywords: Financial Accounting